Chromatin RNA Components - Monahan, John J. (My University, 1973)
Almost all the genetic information of the eucaryotic cell is contained in the nuclear chromosomes. How regulation of the expression of this information takes place still remains as one of the great mysteries of the Biological Sciences. In this thesis an attempt is made to look at a few of the chemical components that may be involved in this process.
Chromatin (the interphase form of the eucaryotic cell genome) of a number of tissue culture cell lines has been fractionated using some novel techniques into its four major components: DNA, RNA, histones and non-histone proteins.
Of these four fractions the RNA fraction has remained the least well characterized. This thesis attempts to demonstrate that the RNA fraction in chromatin, in contrary to the opinion of a number of people at present, a complex fraction, quite distinct from other cellular RNA components. A model is presented whereby gene regulation in eycaryotic cells takes place via the interaction of chromosomal protein and RNA components.
Keywords: Biochemistry; Biochemistry